Answer:
The explicit formula is Tn = 34 + 3n
Step-by-step explanation:
The nth term of an arithmetic sequence can be represented using the formula
Tn = a + (n-1)d
where a is the first term , n is the number of terms and d is the common difference
For the 12 term(a12), n = 12
70 = a + (12-1)d
70 = a + 11d •••••••(i)
For the 30th term, n = 30
124 = a + (30-1)d
124 = a + 29d •••••••(ii)
Now, directly subtract equation i from ii, we have;
124-70 = (a-a) + (29d-11d)
54 = 18d
d = 54/18
d = 3
To get a , we substitute the value of d in any of the equations
let’s use the first
70 = a + 11d
substituting d = 3
70 = a + 11(3)
70 = a + 33
a = 70-33
a = 37
Thus the explicit formula for the nth term will be
Tn = a + (n-1)d
where a = 37 and d = 3
Tn = 37 + (n-1)3
Tn = 37 + 3n -3
Tn = 34 + 3n